Low-temperature directed interesterification increases triunsaturated and trisaturated triacylglycerols of palm oil and affects its thermal, polymorphic and microstructural properties - Nik Mohd Aznizan Nik Ibrahim (2021)
Directed interesterification (DIE) is an interesterification technique performed at a sufficiently low temperature to allow higher melting triacylglycerols (TAG) to crystallise out as they are formed during the reaction. Thus, DIE is an excellent tool for changing the TAG composition of oils and fats and consequently extends their applications. DIE converts liquid oils into plastic fats, reduces the formation of graininess and improves the plasticity of lard, and increases the unsaturation level of the olein fraction of fats. This study explored the possibility of using lipase-catalysed DIE (EDIE) as a ‘green’ technique to produce palm oil (PO) which is high in triunsaturated (U3) and trisaturated (S3) TAG, which in turn, when fractionated, produce an olein fraction which is high in unsaturated (especially, oleic acid) and a stearin fraction that is high in saturated (especially, palmitic acid) fatty acids. EDIE resulted in a significant (p<0.05) increase in U3 and S3 TAG of PO, from 4.3% and 5.2% before EDIE to 27.6% and 31.9% after EDIE, respectively. The increased content of U3 and S3 TAG subsequently altered the physical properties of PO. Higher U3 TAG content led to an increase in the proportion of the low melting fraction of PO. Meanwhile, the melting point, solid fat content at all temperatures and the proportion of high melting fraction of PO show to increase following the rise in S3 TAG after EDIE. A differential scanning calorimetry melting curve showed that the low and high melting fractions of EDIE PO were distinctively separated, indicating ease of fractionation. EDIE also increased the proportion of β crystals in PO. Thus, its microscopic structure showed dense crystal aggregates with a coarse plate-like and orderly packed structure.